2023
DOI: 10.1039/d3ob00606a
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled prebiotic amphiphile-mixture exhibits tunable catalytic properties

Abstract: Protocellular surface formation via the self-assembly of amphiphiles, and catalysis by simple peptides/proto-RNA are two important pillars of the evolution of protocells. To hunt for prebiotic self-assembly-supported catalytic reactions, we...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…At one point, micelles will likely undergo significant morphological transformations, e.g., accumulate compositional mutations leading to micelle-to-vesicle transformation based on lipid geometry variations ( Figure 9 e). Related experiment-based structural changes in the lipid world have been reported [ 32 , 33 , 34 , 35 , 36 , 37 ], including oligo-nucleotide-based amphiphiles and experimental attempts to obtain morphological changes in lipid structures through biomolecular interactions under prebiotic conditions [ 38 , 39 , 40 , 41 , 42 ]. As micelles can join vesicles by membrane fusion, their evolution can be fed into larger and more complex vesicular or even protocellular structures and enrich them with endogenous catalytic synthesis and membrane transport capacities [ 33 , 35 ].…”
Section: Application To Gard Developmentsmentioning
confidence: 99%
“…At one point, micelles will likely undergo significant morphological transformations, e.g., accumulate compositional mutations leading to micelle-to-vesicle transformation based on lipid geometry variations ( Figure 9 e). Related experiment-based structural changes in the lipid world have been reported [ 32 , 33 , 34 , 35 , 36 , 37 ], including oligo-nucleotide-based amphiphiles and experimental attempts to obtain morphological changes in lipid structures through biomolecular interactions under prebiotic conditions [ 38 , 39 , 40 , 41 , 42 ]. As micelles can join vesicles by membrane fusion, their evolution can be fed into larger and more complex vesicular or even protocellular structures and enrich them with endogenous catalytic synthesis and membrane transport capacities [ 33 , 35 ].…”
Section: Application To Gard Developmentsmentioning
confidence: 99%
“…Nanozymes are a class of nanoscale materials that exhibit intrinsic catalytic activity, mimicking the functions of natural enzymes. 1,2 They show unique properties that make them attractive for applications ranging from medical biosensing, 3 treatment of bacterial infections, 4 to environmental remediation. 5 Nanozymes are typically composed of inorganic, metal, or metal oxide nanoparticles that resemble catalytic functions, including peroxidase, oxidase, catalase, and other activities.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group proposed that apart from the anionic amphiphiles, cationic amphiphiles were also important in protocell formation and catalysis. Particularly, we have shown that a lysine-based prebiotic cationic amphiphile and anionic fatty acids may work in tandem (catanionic complex formation) to form a prebiotic membrane at low CVC and assisted in regioselective peptide bond formation . The protocell forming ability of the mixture of cationic amino acid-based amphiphiles (lysine octyl ester, LysOct) and anionic fatty acid amphiphiles (decanoic acid) led to a window of opportunities to explore the capabilities of phosphate- and sulfate-based anionic amphiphiles.…”
Section: Introductionmentioning
confidence: 99%